Process analysis of a production line of aircraft turbine components - Granados Gil, Rafael (2021)
The particular situation of the aeronautical industry in the coming years will force related manufacturing plants to analyze their production processes seeking, among other things that could be remarkable, greater flexibility and efficiency. This article analyzes the manufacturing process of a production line of aircraft turbine components, which faced flow and production capacity problems. The study used the methodology applied by Okutmuş et al. (2015) for data collection, and subsequently, resorted to the methodology used by Molano & Materón (2018) to analyze of the information. Finally, it concludes that production capacity could be increased. Therefore, realistic proposals on the case are presented, which allow improvements in its capacity in the near future.